Intact ketogenesis predicted reduced risk of moderate-severe metabolic-associated fatty liver disease assessed by liver transient elastography in newly diagnosed type 2 diabetes - Lee, Sejeong; Bae, Jaehyun; Kim, Seung Up; Lee, Minyoung; Lee, Yong-ho; Kang, Eun Seok; Cha, Bong-Soo; Lee, Byung-Wan (Frontiers in Endocrinology, 2024)
Aim Hepatic ketogenesis is a key metabolic pathway that regulates energy homeostasis. Some related controversies exist regarding the pathogenesis of metabolic-associated fatty liver disease (MAFLD). We aimed to investigate whether intact ketogenic capacity could reduce the risk of MAFLD based on transient electrography (TE) in patients with newly diagnosed type 2 diabetes (T2D). Methods A total of 361 subjects with newly diagnosed T2D were recruited and classified into two groups based on the median serum β-hydroxybutyrate (βHB) level, referred to as the intact and impaired ketogenesis groups. The glucometabolic relevance of ketogenic capacity and associations of the baseline serum β-HB and MAFLD assessed with TE were investigated. Results Compared to the impaired ketogenesis group, the intact ketogenesis group showed better insulin sensitivity, lower serum triglyceride levels, and higher glycated hemoglobin levels. The controlled attenuation parameter (CAP) was lower in the intact ketogenesis group without statistical significance (289.7 ± 52.1 vs. 294.5 ± 43.6; p=0.342) but the prevalence of moderate–severe steatosis defined by CAP ≥260 dB/m was significantly lower in the intact group. Moreover, intact ketogenesis was significantly associated with a lower risk of moderate–severe MAFLD after adjusting for potential confounders (adjusted odds ratio 0.55, 95% confidence interval 0.30–0.98; p=0.044). Conclusion In drug-naïve, newly diagnosed T2D patients, intact ketogenesis predicted a lower risk of moderate–severe MAFLD assessed by TE.